FORMATION OF VOCAL AND CHORAL SKILLS DURING TEACHING OF STUDENTS OF SINGING - М.V. Viktorova (Academy of Cognitive and Natural Sciences, 2002)
The article deals with the questions of forming of vocal skills in the process of teaching pupils to sing: timbre qualities of voice, breathing, registries, attack of the sound, process of voice-making. The article is addressed to the pedagogical universities teachers on vocal music.